COVID-19: A Boon or a Bane for Creativity? - Mercier, Maxence; Vinchon, Florent; Pichot, Nicolas; Bonetto, Eric; Bonnardel, Nathalie; Girandola, Fabien; Lubart, Todd (Frontiers in Psychology, 2021)
In many countries, the COVID-19 pandemic led to a period of lockdown that impacted individual’s lifestyles, in both professional and personal spheres. Numerous new problems and challenges arose, as well as opportunities. Numerous studies have examined the negative effects of lockdown measures, but few have attempted to shine light on the potential positive effects that may come out of these measures. We focused on one particular positive outcome that might have emerged from lockdown : creativity. To this end, this paper compared professional creativity (Pro-C) and everyday creativity (little-c) before and during lockdown, using a questionnaire-based study conducted on a French sample (N = 1266). We expected participants to be more creative during than prior to lockdown, in both professional and everyday spheres. Regarding professional creativity, we did not see any significant differences between the two comparison points, before and during lockdown. Regarding everyday creativity, we observed a significant increase during lockdown. Furthermore, our results suggest that participants with a lower baseline creativity (before lockdown) benefited more from the situation than those with a higher initial baseline creativity. Our results provide new insights on the impact of lockdown and its positive outcomes. These measures may have inarguably negative consequences on the physical and mental health of many, but their positive impact exists as well.